Қарақалпақ эпосларының сырт ел алымлары тәрепинен үйренилиўиниң жаңа басқышлары (FAN va JAMIYAT, 2022)
The article provides a detailed analysis of the main scientific aspects of the Karakalpak epics studied by foreign scholars on the ex- ample of the epic "Edige". Also, the role of these comparative-typological studies in the history of study of Karakalpak epics abroad will